The nuclear effector of Wnt-signaling, Tcf1, functions as a T-cell-specific tumor suppressor for development of lymphomas. - Machteld M Tiemessen; Miranda R M Baert; Tom Schonewille; Martijn H Brugman; Farbod Famili; Daniela C F Salvatori; Jules P P Meijerink; Ugur Ozbek; Hans Clevers; Jacques J M van Dongen; Frank J T Staal (PLoS Biology)
The HMG-box factor Tcf1 is required during T-cell development in the thymus and mediates the nuclear response to Wnt signals. Tcf1(-/-) mice have previously been characterized and show developmental blocks at the CD4-CD8- double negative (DN) to CD4+CD8+ double positive transition. Due to the blocks in T-cell development, Tcf1(-/-) mice normally have a very small thymus. Unexpectedly, a large proportion of Tcf1(-/-) mice spontaneously develop thymic lymphomas with 50% of mice developing a thymic lymphoma/leukemia at the age of 16 wk. These lymphomas are clonal, highly metastatic, and paradoxically show high Wnt signaling when crossed with Wnt reporter mice and have high expression of Wnt target genes Lef1 and Axin2. In wild-type thymocytes, Tcf1 is higher expressed than Lef1, with a predominance of Wnt inhibitory isoforms. Loss of Tcf1 as repressor of Lef1 leads to high Wnt activity and is the initiating event in lymphoma development, which is exacerbated by activating Notch1 mutations. Thus, Notch1 and loss of Tcf1 functionally act as collaborating oncogenic events. Tcf1 deficiency predisposes to the development of thymic lymphomas by ectopic up-regulation of Lef1 due to lack of Tcf1 repressive isoforms and frequently by cooperating activating mutations in Notch1. Tcf1 therefore functions as a T-cell-specific tumor suppressor gene, besides its established role as a Wnt responsive transcription factor. Thus, Tcf1 acts as a molecular switch between proliferative and repressive signals during T-lymphocyte development in the thymus.